2018
DOI: 10.1002/pc.24955
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in Interfacial Adhesion of Ti/Polyetheretherketone by Electrophoretic Deposition of Graphene Oxide

Abstract: This article discusses about the significance of graphene oxide (GO) deposition on the surface of a titanium plate by electrophoretic deposition (EPD) method to improve the adhesive strength of Ti/polyetheretherketone (PEEK) interfacial adhesive. Firstly, the anodic EPD method was applied to a water dispersion solution of GO, and then the morphology and the properties of titanium plate surface were characterized by scanning electron microscopy and contact angle measurements before and after GO deposition. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…Similar preferential alignment of graphene oxide (GO) nanosheets has been reported in the EPD process [16][17][18][19][20][21]. Furthermore, the incorporation of GO has two main advantages: firstly, the adhesion of GO coatings on metallic substrates after thermal treatment has been attributed to the interaction between the oxygenated functional groups of GO and the metallic surface, and thereby, GO coatings have been used as the interface between PEEK and the metallic substrate to enhance the mechanical properties [21]; secondly, p-conjugated structures in graphitic materials can form strong p-p stacking interactions with the benzene ring such that found in PEEK [22,23]. Nonetheless, direct co-deposition of PEEK/GO by EPD, which should be an attractive route to nanocomposite coatings, has not been explored so far.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Similar preferential alignment of graphene oxide (GO) nanosheets has been reported in the EPD process [16][17][18][19][20][21]. Furthermore, the incorporation of GO has two main advantages: firstly, the adhesion of GO coatings on metallic substrates after thermal treatment has been attributed to the interaction between the oxygenated functional groups of GO and the metallic surface, and thereby, GO coatings have been used as the interface between PEEK and the metallic substrate to enhance the mechanical properties [21]; secondly, p-conjugated structures in graphitic materials can form strong p-p stacking interactions with the benzene ring such that found in PEEK [22,23]. Nonetheless, direct co-deposition of PEEK/GO by EPD, which should be an attractive route to nanocomposite coatings, has not been explored so far.…”
Section: Introductionsupporting
confidence: 68%
“…In this respect, EPD is useful to develop specific microstructures from multicomponent suspensions [14]; for instance, in the study of PEEK/MoS 2 coatings by electrophoretic codeposition, MoS 2 was found to align preferentially, parallel to the coating surface [15]. Similar preferential alignment of graphene oxide (GO) nanosheets has been reported in the EPD process [16][17][18][19][20][21]. Furthermore, the incorporation of GO has two main advantages: firstly, the adhesion of GO coatings on metallic substrates after thermal treatment has been attributed to the interaction between the oxygenated functional groups of GO and the metallic surface, and thereby, GO coatings have been used as the interface between PEEK and the metallic substrate to enhance the mechanical properties [21]; secondly, p-conjugated structures in graphitic materials can form strong p-p stacking interactions with the benzene ring such that found in PEEK [22,23].…”
Section: Introductionmentioning
confidence: 79%
“…The surface energy parameters are listed in Table S2 . The solid surface energy was calculated according to the following formula 12 , 20 where is the measured contact angle; and are the polar part and dispersive part of the solid–gas surface free energy; and are the polar part and dispersive part of the liquid–gas surface free energy; and and represent the surface energies of the liquid and solid surfaces, respectively.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The surface treatment methods of titanium alloy plates can be divided into three categories: (i) mechanical treatments: sandblasting 13 and shock peening; 14 (ii) chemical treatments: anodizing 15 and etching; 16 (iii) the addition of an interfacial layer: sol–gel methods, 17 plasma-spray, 18 coupling agent, 19 and electrophoretic deposition (EPD). 20 All of these treatments can effectively increase the bonding strength between the metal and polymer, thereby enhancing the interface. Among them, EPD is a simple, generic, and reliable room-temperature method for coating nanomaterials (including CNTs) on conductive substrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation